Nurses’ Knowledge of First Aid Management of Burn Patients at the Peshawar Burn and Plastic Surgery Center: Nurses’ Knowledge of First Aid Management of Burn Patients - Anwar, Muhammad; Ali Shah, Bakhtyar; Muhammad, Dildar; Sultan, Amir; Tariq, Muzamil; Akhtar, Naheed; Hussain, Shah (Pakistan Journal of Health Sciences, 2023)
A burn is an injury to the skin and tissues caused by chemical, electricity, radiation or heat. Burn injuries cause a relatively high morbidity and mortality rates worldwide. Objective: to assess first aid knowledge of nurses working in burn centers. Methods: A descriptive cross-sectional design with a sample size of 84 using an appropriate sampling technique was used in the study. The study was conducted in July 2022 and he August at the Peshawar Burn and Plastic Surgery Center. The instrument used for data collection was his 10-item self-structured questionnaire with a Chronbach alpha reliability of 0.87. SPSS version 24.0 was used to calculate frequencies and percentages for categorical variables. Results: Overall, 56% of participants reported having a good knowledge of burns, while 32% of participants reported being average, and 12% of participants reported first aid for burn patients reported low knowledge. Conclusions: This study concluded that nurses working in burn and plastic surgery departments have good knowledge of first aid administration